Active Anti-jerking Control of Shifting for Electric Vehicle Driveline. (December 2016) - Lin, Cheng; Sun, Shengxiong; Jiang, Wenfei
Abstract: Electric vehicles play an increasingly important role in modern intelligent transportation, as a critical component of electric vehicle, driveline with better dynamic performance will bring better driving experience. There is no clutch to buffer step change of torque, tortional vibration will occur when shifting. In this paper, according to the structure of electric vehicle, dynamic model of driveline is developed, based on the state space equation, optimal feedback controller is proposed to interrupt power input and prevent the driveline from tortional vibration by controlling the torque input actively when shifting. Simulation results demonstrate the optimal control of motor torque can reduce tortional vibration in driveline significantly.